Notch pathway activation enhances cardiosphere in vitro expansion. Issue 11 (23rd August 2018) - Secco, Ilaria; Barile, Lucio; Torrini, Consuelo; Zentilin, Lorena; Vassalli, Giuseppe; Giacca, Mauro; Collesi, Chiara
Abstract: Cardiospheres (CSps) are self‐assembling clusters of a heterogeneous population of poorly differentiated cells outgrowing from in vitro cultured cardiac explants. Scanty information is available on the molecular pathways regulating CSp growth and their differentiation potential towards cardiac and vascular lineages. Here we report that Notch1 stimulates a massive increase in both CSp number and size, inducing a peculiar gene expression programme leading to a cardiovascular molecular signature. These effects were further enhanced using Adeno‐Associated Virus (AAV)‐based gene transfer of activated Notch1‐intracellular domain (N1‐ICD) or soluble‐Jagged1 (sJ1) ligand to CSp‐forming cells. A peculiar effect was exploited by selected pro‐proliferating miRNAs: hsa‐miR‐590‐3p induced a cardiovascular gene expression programme, while hsa‐miR‐199a‐3p acted as the most potent stimulus for the activation of the Notch pathway, thus showing that, unlike in adult cardiomyocytes, these miRNAs involve Notch signalling activation in CSps. Our results identify Notch1 as a crucial regulator of CSp growth and differentiation along the vascular lineage, raising the attracting possibility that forced activation of this pathway might be exploited to promote in vitro CSp expansion as a tool for toxicology screening and cell‐free therapeutic strategies.